Preparation of Ag decorated TiO2 substrates for surface-enhanced raman scattering - Le Minh Thuy; Le Thi Ngoc Loan (My University, 2021)
Preparation of Ag decorated TiO2 substrates for surface-enhanced raman scattering
Keywords: Đế SERS; TiO2 gắn Bạc (Ag); Tăng cường phổ Raman